2019
DOI: 10.48084/etasr.2494
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Strength of Reinforced Concrete RAC Beams Exposed to 6-hour Fire – Part 2: Rich Mix

Abstract: In this research work, experimental investigation on flexural strength of reinforced concrete beams exposed to fire for 6-hours at the temperature of 1000˚C is presented. The beams are made with 50% replacement of natural coarse aggregates with recyclable concrete aggregates. A total of 12 reinforced concrete beams using 1:1.5:3 mix (rich mix) and 0.54 water-cement ratio were cast. The beams were prepared in two groups. Group 1 beams were prepared with 50% recyclable aggregates, whereas group 2 beams were cast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…These stresses contribute to a decrease in the critical buckling load and must be considered during the design process. Many studies investigated the effect of multiple web openings along the span length of RC beams [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…These stresses contribute to a decrease in the critical buckling load and must be considered during the design process. Many studies investigated the effect of multiple web openings along the span length of RC beams [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Authors in [9] showed that the increase in temperature has significant impact on the compressive and flexural tensile strength of concrete. However, there is no effect on strength when hard concrete is exposed to 6-hour fire at 1000°C [13]. Authors in [5,14] reported that the effect of heat treatment on the modulus of elasticity is the same as that on strength.…”
Section: Introductionmentioning
confidence: 99%